Systematic Literature Review: Efektivitas Pembelajaran Mendalam Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Menegah Atas - Ilhamurrahman M Hubaib; Siti Hardiyanti Triana (INDO PUBLISHING, 2026)
This study aims to examine the effectiveness of deep learning in enhancing the critical thinking skills of high school (SMA) students. A systematic literature review was conducted by searching for articles on Google Scholar using the